COVID-19 burnout, resilience, and psychological distress among Chinese college students - Sun, YueYi; Zhu, ShuYue; ChenHuang, GanXin; Zhu, LiYa; Yang, ShuHan; Zhang, XiaoCong; Zheng, Zheng (Frontiers in Public Health, 2022)
Background: Since the outbreak of COVID-19, Chinese college students have spent three years dealing with infection prevention. Some students have undergone quarantine because of the detection of new variants of COVID-19 and rise in cases. This study examines pandemic-related isolation and its psychological impact on Chinese college students and explores the relationships among COVID-19 burnout, resilience, and psychological distress in Chinese college students during the pandemic. Methods: The COVID-19 Burnout Scale, the Connor-Davidson Resilience Scale, and the Brief Symptom Inventory were used to investigate 388 college students from Nanjing City, China. All participants had enrolled in university after 2019, and they participated in the survey voluntarily via the Internet. Participants were divided into two groups (isolated group versus non-isolated group) based on whether or not they had been isolated. Results: (1) Significantly lower scores were found for all factors in the isolated group; (2) COVID-19 burnout significantly negatively predicted resilience and significantly positively predicted psychological distress (anxiety, depression, and somatization symptoms), while resilience significantly negatively predicted psychological distress; (3) Resilience mediated the relationship between COVID-19 burnout and psychological distress. Conclusions: Isolation is a risk factor for psychological distress related to COVID-19. Resilience can buffer psychological distress and help improve Chinese college students' well-being during the COVID-19 pandemic.